The Role of Subcutaneous Ketorolac for Pain Management. Issue 2 (February 2015) - Vacha, Mary E.; Huang, Wennie; Mando-Vandrick, Jennifer
This Hospital Pharmacy feature is extracted from Off-Label Drug Facts, a publication available from Wolters Kluwer Health. Off-Label Drug Facts is a practitioner-oriented resource for information about specific drug uses that are unapproved by the US Food and Drug Administration. This new guide to the literature enables the health care professional or clinician to quickly identify published studies on off-label uses and determine if a specific use is rational in a patient care scenario. References direct the reader to the full literature for more comprehensive information before patient care decisions are made. Direct questions or comments regarding Off-Label Drug Uses tojgeneral@ku.edu .